Conversation Analysis as a Discourse Approach to Teaching Speaking Skill - Dinar Dipta (JETLe (Journal of English Language Teaching and Learning), 2019)
Conversation comes as two ways communication used in daily activities. The large numbers of conversations lead some researchers to analyze it. Conversation has been the primary interest to language researchers since natural, unplanned, everyday conversation is the most commonly occurring and universal language genre (Riggenbach, 1999). Conversation is a speech activity in which all members of a community routinely participate. Among other approaches to discourse analysis used in teaching speaking, conversation analysis (CA) is one of the convenient practical devices in teaching oral English in the classroom. This paper aims to explore the theoretical basis for conversational analysis and examine the techniques applying a discourse approach to teaching speaking in the classroom.